Investigation of cyclodextrin as potential carrier for lycopene - Kulawik, Anna; Rosiak, Natalia; Miklaszewski, Andrzej; Cielecka-Piontek, Judyta; Zalewski, Przemysław (Archives of Pharmacy, 2024)
Lycopene is a carotenoid with high antioxidant activity. Numerous studies show its positive effects in the prevention and amelioration of many diseases. However, due to its lack of water solubility, its use is very limited. Developing a formulation with lycopene with favorable therapeutic parameters will allow for a more effective use of this ingredient. The aim of this study was therefore to use supercritical phase extraction to obtain lycopene-containing preparations, and to obtain complexes of the extract with cyclodextrins to improve its solubility and increase its antioxidant potential. Lycopene-containing extracts were obtained by ultrasound-assisted acetone extraction and supercritical phase extraction. The supercritical extract was combined with γ-cyclodextrin, β-cyclodextrin and 2-hydroxypropyl-β-cyclodextrin. Attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) and X-ray diffraction (XRD) analyses were performed for the obtained systems and extracts. A paddle apparatus was used to evaluate the in vitro dissolution, and the samples collected were analysed by HPLC. The antioxidant activity was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical method. The results show that cyclodextrins increase the dissolution of lycopene into an acidic environment and enhance the antioxidant potential of the compound. We conclude that the development of a formulation containing a combination of lycopene obtained by supercritical extraction and cyclodextrin will allow for a wider and more effective use of this ingredient.
Keywords: lycopene; supercritical phase extraction; cyclodextrins; drug delivery system; antioxidant